Aplicação de Impressões 3D como recurso didático para o ensino do componente curricular estruturas de aço na UFERSA-CMPF - Queiroz, José Henrique Maciel de (Universidade Federal Rural do Semi-Árido, 2018)
The teaching-learning process has several challenges that the teacher must overcome along with his students, using the available methods, techniques and resources. At the Universidade Federal Rural do Semi-Árido, Centro Multidisciplinar Pau dos Ferros, one of the difficulties presented by the students of the curricular component Structures of Steel in the semester 2018.1 is to visualize and understand two-dimensional representations exposed in examples on the chalkboard, exercises and present questions in evaluation activities. Aiming to provide alternatives to overcome this problem, it is proposed in this work the adoption of a technology that has attracted a lot of attention currently in several market segments: 3D printing. With a 3D printer were constructed, pieces representative of elements commonly present in the design of metal structures and that consequently are explained by the teacher in his class. These pieces were used, experimentally, to complement the didactics of the teacher from the second unit of the curricular component, exposing concepts in a more interactive and realistic way. Qualitatively, the perception of the members of the class in relation to this didactic resource was evaluated, showing its importance and impact on students' learning. All the students interviewed during the research were satisfied with the implementation of the technology in class, emphasizing that it really helped them in the assimilation of the concepts discussed in the scope of the Steel Structures component. It was realized throughout the work that this type of solution is approved by the students and that, for them, is a good way to complement their training.
Keywords: Impressão 3D; Estruturas de aço; Ensino; Didática; ENGENHARIAS::ENGENHARIA CIVIL